2012
DOI: 10.1523/jneurosci.0045-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Sleep Deprivation Downregulates Dopamine D2R in Ventral Striatum in the Human Brain

Abstract: Dopamine D2 receptors are involved with wakefulness but their role in the decreased alertness associated with sleep deprivation is unclear. We had shown that sleep deprivation reduced dopamine D2/D3 receptor availability (measured with PET and [11C]raclopride in controls) in striatum, but could not determine if this reflected dopamine increases ([11C]raclopride competes with dopamine for D2/D3 receptor binding) or receptor downregulation. To clarify this, we compared the dopamine increases induced by methylphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
155
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(161 citation statements)
references
References 53 publications
(58 reference statements)
5
155
1
Order By: Relevance
“…In accordance with this hypothesis, the functional availability of mGlu5 receptors in a striatal region including the NAc is enhanced compared to baseline after the experimental deprivation of one night of sleep in humans [105]. Intriguingly, the same procedure was found to reduce dopamine D 2/3 receptor availability in the ventral striatum by almost the identical magnitude (~5 %) [100]. Taken together, the convergent findings may indirectly support the notion that A 2A -mGlu5-D 2 receptor heteromers modulate the quality of wakefulness and sleep via the NAc.…”
Section: Adenosine Receptor Heteromers and Receptor-receptor Interactsupporting
confidence: 55%
See 1 more Smart Citation
“…In accordance with this hypothesis, the functional availability of mGlu5 receptors in a striatal region including the NAc is enhanced compared to baseline after the experimental deprivation of one night of sleep in humans [105]. Intriguingly, the same procedure was found to reduce dopamine D 2/3 receptor availability in the ventral striatum by almost the identical magnitude (~5 %) [100]. Taken together, the convergent findings may indirectly support the notion that A 2A -mGlu5-D 2 receptor heteromers modulate the quality of wakefulness and sleep via the NAc.…”
Section: Adenosine Receptor Heteromers and Receptor-receptor Interactsupporting
confidence: 55%
“…More specifically, brain imaging studies revealed that dopamine D 2 receptors are downregulated in NAc and ventral striatum following sleep deprivation and that the decrease correlates with reduced cognitive performance [99,100]. Furthermore, the functional polymorphism rs28363170 of the gene encoding DAT (SLC6A3 or DAT1) modulates neurophysiological markers of sleep homeostasis and the effects of caffeine on these markers in NREM sleep [101•].…”
Section: Adenosine Receptor Heteromers and Receptor-receptor Interactmentioning
confidence: 99%
“…Because the insular cortex is activated during both NREM (Nofzinger et al 2002) and REM sleep (Maquet et al 2000), one could hypothesize that SD interferes with emotional functions subserved by the insula. Moreover, decreases in D2/D3 receptor availability may account for impairments in performance, reward learning, and decision making after SD (Volkow et al 2012). Indeed, insufficient sleep is associated with changes in reward-related decision making: people take greater risks (Harrison and Horne 2000) and are less concerned with the negative consequences of their risky behaviors (Chee and Chuah 2008;Venkatraman et al 2007Venkatraman et al , 2011.…”
Section: Sleep Disturbance Causes Waking Emotional Dysfunctionsmentioning
confidence: 99%
“…Similarly, Holst et al (2014) found that human homozygotic carriers of an allele of the dopamine transporter that reduces dopamine transporter availability (10R/10R, Costa, Riedel, Müller, Möller, & Ettinger, 2011) had a greater SWA rebound after sleep deprivation. It is yet to be determined whether this SWA rebound is associated with the downregulation of D2/D3 receptors (Volkow et al, 2012). However, as increased synaptic dopamine in the striatum induces the homeostatic SWA response, consistent with the notion that excess dopamine in this region results in synaptic scaling (Thomas et al, 2008), potentially postdrug administration SWS is involved in the strengthening of behavioral patterns associated with the drug.…”
Section: Shared Neurobiological Substrates Of Sleep and Addictionsmentioning
confidence: 91%
“…A series of studies by Volkow and colleagues (Volkow et al, 2008(Volkow et al, , 2009(Volkow et al, , 2012, using positron emission tomography, found downregulation of dopamine D2/D3 receptors in the ventral striatum after one night of sleep deprivation and that these changes were associated with impaired performance on a visual attention task. This suggests that prolonged wake activates synaptic mechanisms that reduce sensitivity to dopamine, similar to the changes observed after repeated drug use.…”
Section: Sleep Disturbance and Basmentioning
confidence: 99%